A Note on the Effects of a Changing Deficit - Salant, Walter S. (Quarterly Journal of Economics, 1939)
Journal Article A Note on the Effects of a Changing Deficit Get access Walter S. Salant Walter S. Salant Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 2, February 1939, Pages 298–304, https://doi.org/10.2307/1882891 Published: 01 February 1939